Uji Berbagai Varietas Cabai Merah Pada Tanah Alluvial - Imanuel Martono Deo; Setia Budi; Tatang Abdurrahman (Jurnal Sains Pertanian Equator, 2020)
The aim of this research is to find out the best variety to the growth and yield of red chillies on alluvial soil. The research was conducted from 16 march to 12 june 2019 in Jl. Siaga, Gg. Siaga Setia,Kubu Raya. The study used a completely randomized design (CRD) method in which the application of variety on red chillies as a single factor. The research consists of 4 treatments with 6 replications and each replication consisted of 4 sample plants. The treatment in question is p1 = Hot Beauty Variety, p2 = Hot Chilli Variety, p3 = Gada F1 Variety dan p4 = Passion Variety. The observed variables in this study are plant height, root volume, the number of fruit per plant, diameter of fruit per plant and weight of fruit per plant. Results of the research shows that variety of Gada f1 and hot chilli variety are able to provide the best tolerance if compared to the hot beauty variety and passion in alluvial soil and environmental plants, their products are not yet out of the product. Keywords : red chili, , variety. alluvial soil